Physiotherapy student´s perceptions of the problem based learning curriculum implementation process - Macedo, Rui (2021)
The Bologna declaration process was an opportunity for a major change in Physiotherapy curriculum at Escola Superior de Saúde do Porto – Portugal. In 2008-2009 school year a Problem Based Learning curriculum was adopted. Literature and a previous study pointed to student’s resistance and to problems associated with the implementation of this new aproach. Regular meetings with student’s where put in place in order to deal with this anticipated problems. For each meeting there was a written record. For each curricular year, three or more Curricular Units produced regular meetings. Two or more meeting records were produced in most Curricular Units. The aim of this study is to understand the perceptions of 1st, 2nd and 3rd year Physiotherapy students about the PBL approach, during the first year of implementation. A Corpus of 24 records from the 1st, 2nd and 3th year meetings was submitted to Thematic Content Analysis by two referees which agreed on a posteriori categorical system. Peer debriefing was used to ensure trustworthiness and authenticity. The analysis revealed 4 dimensions – Means, Organization, Curriculum, Assessment - which included all themes relating to major areas of concern. Major concerns changed throughout the curricular units and throughout the year and differed from student’s curricular year. Means strongly influenced the other dimensions. Organization problems resulted mainly from lack of experience of curriculum designers. Curriculum dimension reveals some misunderstanding of Problem Based Learning both from students and teachers whereas Assessment problems relate mainly to subjects, methods and the timing of information to students.